Composite excitation grouting material and preparation method thereof

By using active excitants such as calcium sulfaluminate, gypsum, sodium hydroxide, sodium silicate water glass and other active excitants in the grouting material, the problem of poor construction performance and volume stability of traditional grouting materials is solved. A composite excitation grouting material with high compressive strength and good construction ease is achieved.

CN119241150APending Publication Date: 2025-01-03LIAONING INST OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411394893.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Traditional inorganic polymer grouting materials have poor construction performance and poor volume stability, which cannot meet the requirements of infrastructure construction.

Method used

Using composite excitation grouting material, mixing slag and fly ash in a specific proportion, and using calcium sulfaluminate, gypsum, sodium hydroxide, and sodium silicate water glass as active exciters, and mixing and stirring with auxiliary agents to form Grouting material with excellent compressive resistance and construction ease.

Benefits of technology

The high compressive strength and good volume stability of the grouting material are achieved. The compressive strength of 1d is greater than 20Mpa, the compressive strength of 3d is greater than 40MPa, and the compressive strength of 28d is greater than 70Mpa. The initial flow degree and 20min flow degree meet the national standards, and the volume deformation rate Within 5% of ten thousand.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to a composite excitation grouting material and a preparation method thereof. The composite exciting grouting material is prepared from the following raw materials in parts by weight: 300 to 700 parts of precursor, 50 to 400 parts of active exciting agent, 400 to 1200 parts of solid waste aggregate and 5 to 100 parts of auxiliary agent, wherein the precursor is a mixture of slag and fly ash in a mass ratio of (1: 0.2)-(1: 1.5); the active exciting agent is a mixture of calcium sulphoaluminate, gypsum, sodium hydroxide and sodium silicate water glass in a weight part ratio of (200-300): (50-100): (15-25): (50-70). The active exciting agent is selected from calcium sulphoaluminate, gypsum, sodium hydroxide and sodium silicate water glass, so that the grouting material prepared from the slag and the fly ash under the synergistic effect of the composite exciting agent has excellent compression resistance, construction workability and volume stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a composite stimulating grouting material and a preparation method thereof. Background Art

[0002] Inorganic polymers are based on silicon-aluminum precursors, and through the dissolution and polymerization of aluminum-oxygen tetrahedrons and silicon-oxygen tetrahedrons, a green gelling system with good durability is formed. With the continuous development of infrastructure construction, higher requirements are put forward for silicon-aluminum inorganic polymer gelling systems. The traditional method of using strong alkali to activate the polymers of slag and fly ash alone has poor construction performance and poor volume stability, and does not meet the requirements of the grouting material construction environment.

[0003] Therefore, in order to solve the problems of poor workability and poor volume stability of inorganic polymer grouting materials in the prior art, it is necessary to provide a new inorganic polymer grouting material that can solve the above problems. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a composite stimulating grouting material and a preparation method thereof.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] On the one hand, the present invention provides a composite stimulating grouting material, comprising the following raw materials in parts by weight: 300-700 parts of a precursor, 50-400 parts of an active activator, 400-1200 parts of solid waste aggregate, and 5-100 parts of an additive; wherein the precursor is a mixture of slag and fly ash in a mass ratio of 1:0.2 to 1:1.5; the active activator is a mixture of calcium sulfoaluminate, gypsum, sodium hydroxide, and sodium silicate water glass in a weight ratio of 200-300:50-100:15-25:50-70.

[0007] Optionally, the particle size of the slag is 5 to 45 μm, and the particle size of the fly ash is 10 to 100 μm.

[0008] Optionally, the modulus of sodium silicate water glass is 1.2-1.7; and the gypsum is one or more of anhydrite, dihydrate gypsum, and hemihydrate gypsum.

[0009] Optionally, the auxiliary agent is a mixture of naphthalene-based water reducer, borax, sodium dihydrogen phosphate, defoamer, cellulose ether and fiber in a mass ratio of 8-12:5-8:1-4:0.2-0.6:0.1-0.3:2-10.

[0010] Optionally, the cellulose ether is one or more of 400 viscosity hydroxypropyl methyl cellulose ether, 100,000 viscosity hydroxypropyl methyl cellulose ether, and 200,000 viscosity hydroxypropyl methyl cellulose ether.

[0011] Optionally, the defoaming agent is one or more of a mineral oil defoaming agent, a polyether-modified silicon defoaming agent and a fatty acid defoaming agent.

[0012] Optionally, the fiber is one or more of polypropylene fiber, basalt fiber and carbon fiber.

[0013] Optionally, the solid waste aggregate is iron tailings sand.

[0014] Optionally, the particle size of the iron tailings sand ranges from 10 to 150 meshes.

[0015] The present invention provides a composite stimulating grouting material. By selecting calcium sulfoaluminate, gypsum, sodium hydroxide, sodium silicate water glass as the active activator, the grouting material prepared by slag and fly ash under the synergistic action of the composite activator can have excellent compressive performance, as well as excellent construction workability and volume stability; wherein the compressive performance of the grouting material is specifically 1d compressive strength greater than 20Mpa, 3d compressive strength greater than 40MPa, and 28d compressive strength greater than 70MPa; the grouting material has high construction workability and good volume stability, specifically according to the "JCT985-2017 National Standard for Cement-based Self-leveling Mortar for Ground Use", the initial fluidity is 135mm, the 20min fluidity is 130mm, and the volume deformation is within 5 ten-thousandths. It can be seen that the grouting material provided by the present application can be widely used in foundation grouting.

[0016] Another aspect of the present invention provides a method for preparing a sulfur-alkali composite activated all-solid waste grouting material, comprising: weighing a precursor, an active activator, solid waste aggregate and an additive according to the weight proportions of any of the above-mentioned implementation methods, and then mixing the precursor, the active activator, the solid waste aggregate and the additive to obtain a composite activated grouting material.

[0017] The preparation method of the composite activated grouting material provided by the present invention comprises the following steps: selecting a mixture of slag and fly ash as a precursor, and then weighing the precursor, an active activator, solid waste aggregate and an auxiliary agent and mixing them to obtain the grouting material. Not only is the preparation method simple, but the obtained grouting material also has excellent construction workability and volume stability.

[0018] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structure particularly pointed out in the written description.

[0019] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] A composite activating grouting material provided in an embodiment of the present invention comprises the following raw materials in parts by weight: 300-700 parts of a precursor, 50-400 parts of an active activator, 400-1200 parts of solid waste aggregate, and 5-100 parts of an additive; wherein the precursor is a mixture of slag and fly ash in a mass ratio of 1:0.2 to 1:1.5; the active activator is a mixture of calcium sulfoaluminate, gypsum, sodium hydroxide, and sodium silicate water glass in a weight ratio of 200-300:50-100:15-25:50-70.

[0022] Here, the active activator is selected as a mixture of calcium sulfoaluminate, gypsum, sodium hydroxide, and sodium silicate water glass, replacing the traditional active activator composed of sodium hydroxide and sodium silicate water glass. After the precursor is excited by sodium hydroxide and sodium silicate water glass, the prepared grouting material has a higher compressive strength. Calcium sulfoaluminate and gypsum produce calcium sulfoaluminate with expansion properties, so that the calcium sulfoaluminate can play a role in compensating the shrinkage of the inorganic polymer system; in addition, the sulfate ions produced by calcium sulfoaluminate and gypsum by dissolving in water can jointly excite slag and fly ash with the hydroxide ions produced by the traditional strong alkali (sodium hydroxide), so as to accelerate the dissolution and subsequent polymerization of cations in slag and fly ash, and then promote the formation of a more compact three-dimensional network structure of slag and fly ash, so that the grouting material can form an inorganic polymer with excellent performance. Of course, the mass ratio between calcium sulfoaluminate, gypsum, sodium hydroxide, and sodium silicate water glass is determined by the inventor through a large number of experiments, and it is controlled within an appropriate range to fully reduce the cost while achieving the best performance.

[0023] In this embodiment, by selecting calcium sulfoaluminate, gypsum, sodium hydroxide, and sodium silicate water glass as active activators, slag and fly ash can be made to form a grouting material with excellent construction workability and volume stability under the synergistic effect of calcium sulfoaluminate, gypsum, sodium hydroxide and sodium silicate water glass; the compressive properties of the grouting material are specifically 1d compressive strength greater than 20Mpa, 3d compressive strength greater than 40MPa, and 28d compressive strength greater than 70MPa; the grouting material has high construction workability and good volume stability, specifically according to the "JCT985~2017 National Standard for Cement-based Self-leveling Mortar for Ground Use", the initial fluidity is 135mm, the 20min fluidity is 130mm, and the volume deformation is within 5 ten-thousandths. It can be seen that the grouting material provided in this application can be widely used in foundation grouting.

[0024] In some possible embodiments, the particle size of slag is 5 to 45 μm, and the particle size of fly ash is 10 to 100 μm.

[0025] It should be noted that according to the dense packing theory, experiments have found that when the slag particle size is 5-45 μm, the steel slag particle size is 5-45 μm, and the fly ash particle size is 10-100 μm, the grouting material finally prepared has high activity and can also meet the requirements of dense packing, so that the grouting material has high fluidity and excellent volume stability. Of course, the particle size ranges corresponding to slag and fly ash are determined by the inventor through a large number of experiments. Controlling them within an appropriate range can fully reduce costs while achieving the best performance.

[0026] Exemplarily, the particle size of slag includes but is not limited to 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm and 45μm, and the particle size of fly ash includes but is not limited to 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm and 100μm.

[0027] In this embodiment, by selecting the particle size of slag to be 5-45 μm and the particle size of fly ash to be 10-100 μm, the requirement of dense stacking can be met, so that the grouting material added with the above slag and fly ash has higher fluidity and excellent volume stability.

[0028] In some possible embodiments, the modulus of sodium silicate water glass is 1.2-1.7; the gypsum is one or more of anhydrite, dihydrate gypsum, and hemihydrate gypsum.

[0029] In this embodiment, because water glass with different moduli has different excitation effects on the precursor, the modulus of water glass is selected to be in the range of 1.2 to 1.7, which is determined by the inventor through a large number of experiments. The compressive strength of the grouting material corresponding to this range is the largest. At the same time, it can be analyzed in the experiment that when the modulus of water glass is greater than 1.7, the compressive strength of the system decreases with the increase of the modulus. Therefore, the modulus of water glass is selected to be 1.2 to 1.7.

[0030] In some possible embodiments, the auxiliary agent is a mixture of naphthalene-based water reducer, borax, sodium dihydrogen phosphate, defoamer, cellulose ether and fiber in a mass ratio of 8-12:5-8:1-4:0.2-0.6:0.1-0.3:2-10.

[0031] Here, naphthalene-based water reducer is a surfactant with a dispersing effect; in addition, the encapsulation and organic chelation between borax and sodium dihydrogen phosphate can play a composite retarding effect; the defoamer has the effect of reducing the surface tension of bubbles, which can achieve the effect of rapid bubble breaking, reduce the internal pores of the grouting material, and make the surface gloss of the grouting material higher; cellulose ether has the effect of water retention and thickening to reduce the exudation of the grouting material; the fiber can ensure the flexural and tensile strength of the grouting material, ensure that the volume does not shrink during the entire hydration process, and reduce the risk of cracking.

[0032] It should be noted that the mass ratio ranges of naphthalene-based water reducer, borax, sodium dihydrogen phosphate, defoamer, cellulose ether and fiber are determined by the inventors through a large number of experiments, and are controlled within an appropriate range to achieve optimal performance while fully reducing costs.

[0033] Furthermore, the cellulose ether is one or more of 400 viscosity hydroxypropyl methyl cellulose ether, 100,000 viscosity hydroxypropyl methyl cellulose ether, and 200,000 viscosity hydroxypropyl methyl cellulose ether.

[0034] In this embodiment, by selecting one or more of 400 viscosity hydroxypropyl methyl cellulose ether, 100,000 viscosity hydroxypropyl methyl cellulose ether, and 200,000 viscosity hydroxypropyl methyl cellulose ether as the cellulose ether, the cellulose ether can have a better water-retaining and thickening effect, thereby reducing the occurrence of water seepage in the grouting material.

[0035] Furthermore, the defoaming agent is one or more of a mineral oil defoaming agent, a polyether-modified silicon defoaming agent and a fatty acid defoaming agent.

[0036] In this embodiment, the defoaming agent is selected as one or more of mineral oil defoaming agents, polyether modified silicon defoaming agents and fatty acid defoaming agents, which can reduce the surface tension of bubbles in the grouting material, reduce the internal pores of the grouting material, and make the surface gloss of the grouting material higher.

[0037] Furthermore, the fiber is one or more of polypropylene fiber, basalt fiber and carbon fiber.

[0038] In this embodiment, the fiber is one or more of polypropylene fiber, basalt fiber and carbon fiber, which can better inhibit the volume shrinkage of the grouting material system in the early and late stages of hydration, ensure that the volume does not shrink during the entire hydration process, and reduce the risk of cracking.

[0039] Furthermore, the solid waste aggregate is iron tailings sand.

[0040] In this embodiment, by selecting solid waste aggregate as iron tailings sand, the iron tailings sand can be reused to achieve the purpose of treating waste with waste.

[0041] Furthermore, the particle size of the iron tailings sand ranges from 10 to 150 meshes.

[0042] Preferably, the particle size of the iron tailings sand is in the range of 40 to 150 meshes.

[0043] Here, the particle size range of 40-150 mesh of iron tailings is determined by the inventor through a large number of experiments, and the performance is optimized while the cost is fully reduced by controlling it within an appropriate range. Among them, the particle size of iron tailings includes but is not limited to 40 mesh, 50 mesh, 60 mesh, 70 mesh, 80 mesh, 90 mesh and 100 mesh.

[0044] The present invention provides a method for preparing a composite stimulating grouting material, comprising: weighing a precursor, an active stimulator, solid waste aggregate and an auxiliary agent according to the weight proportions of any of the above embodiments, and then mixing the precursor, the active stimulator, the solid waste aggregate and the auxiliary agent to obtain a grouting material.

[0045] In this embodiment, the grouting material is obtained by selecting the precursor as a mixture of slag and fly ash, and then weighing the precursor, active activator, solid waste aggregate and additives and mixing them. Not only is the preparation method simple, but the obtained grouting material also has excellent construction workability and volume stability.

[0046] The following is a detailed description of a composite stimulating grouting material and a preparation method thereof provided by the present invention through examples.

[0047] Example 1

[0048] The present embodiment provides a composite stimulating grouting material, which includes the following raw materials in parts by weight: 350 parts of slag, 150 parts of fly ash, 800 parts of iron tailings, 200 parts of calcium sulfoaluminate, 50 parts of anhydrite, 20 parts of sodium hydroxide, 60 parts of sodium silicate water glass, 10 parts of naphthalene-based water reducer, 5 parts of borax, 3 parts of sodium dihydrogen phosphate, 0.2 parts of polyether modified silicon defoamer, 0.3 parts of 100,000 viscosity hydroxypropyl methylcellulose ether, and 2 parts of 6mm polypropylene fiber.

[0049] Among them, the particle size of slag is 10-40 μm, the particle size of fly ash is 50-60 μm; the modulus of water glass is 1.5; and the particle size range of iron tailings is 10-100 meshes.

[0050] The present embodiment provides a method for preparing an alkali-activated grouting material, comprising: weighing slag, fly ash, iron tailings, calcium sulfoaluminate, anhydrite, sodium hydroxide, sodium silicate water glass, naphthalene-based water reducer, borax, sodium dihydrogen phosphate, polyether-modified silicon defoamer, 100,000 viscosity hydroxypropyl methylcellulose ether and 6 mm polypropylene fiber according to the above weight portions, mixing and stirring to obtain the grouting material.

[0051] The grouting material prepared in this embodiment has a 1d compressive strength of 22 MPa, a 3d compressive strength of 38 MPa, and a 28d compressive strength of 66 MPa. According to the "JCT985-2017 National Standard for Cement-Based Self-Leveling Mortar for Floors", the initial fluidity of the grouting material measured is 134 mm, the 20-min fluidity is 130 mm, and the volume deformation rate is 4 ten-thousandths of shrinkage.

[0052] Example 2

[0053] The present embodiment provides a composite stimulating grouting material, comprising the following raw materials in parts by weight: 350 parts of slag, 150 parts of fly ash, 800 parts of iron tailings, 300 parts of calcium sulfoaluminate, 50 parts of anhydrite, 20 parts of sodium hydroxide, 60 parts of sodium silicate water glass, 10 parts of naphthalene-based water reducer, 5 parts of borax, 3 parts of sodium dihydrogen phosphate, 0.2 parts of polyether modified silicon defoamer, 0.3 parts of 100,000 viscosity hydroxypropyl methylcellulose ether, and 2 parts of 6mm polypropylene fiber.

[0054] Among them, the particle size of slag is 10-40 μm, the particle size of fly ash is 50-60 μm; the modulus of water glass is 1.5; and the particle size range of iron tailings is 10-100 meshes.

[0055] The present embodiment provides a method for preparing an alkali-activated grouting material, comprising: weighing slag, fly ash, iron tailings, calcium sulfoaluminate, anhydrite, sodium hydroxide, sodium silicate water glass, naphthalene-based water reducer, borax, sodium dihydrogen phosphate, polyether-modified silicon defoamer, 100,000 viscosity hydroxypropyl methylcellulose ether and 6 mm polypropylene fiber according to the above weight portions, mixing and stirring to obtain the grouting material.

[0056] The grouting material prepared in this embodiment has a 1d compressive strength of 28 MPa, a 3d compressive strength of 40 MPa, and a 28d compressive strength of 69 MPa. According to the "JCT985-2017 National Standard for Cement-Based Self-Leveling Mortar for Floors", the initial fluidity of the grouting material measured is 133 mm, the 20-min fluidity is 130 mm, and the volume deformation rate is 3.5 ten-thousandths of shrinkage.

[0057] Example 3

[0058] The present embodiment provides a composite stimulating grouting material, comprising the following raw materials in parts by weight: 350 parts of slag, 150 parts of fly ash, 800 parts of iron tailings, 200 parts of calcium sulfoaluminate, 100 parts of anhydrite, 20 parts of sodium hydroxide, 60 parts of sodium silicate water glass, 10 parts of naphthalene-based water reducer, 5 parts of borax, 3 parts of sodium dihydrogen phosphate, 0.2 parts of polyether modified silicon defoamer, 0.3 parts of 100,000 viscosity hydroxypropyl methylcellulose ether, and 2 parts of 6mm polypropylene fiber.

[0059] Among them, the particle size of slag is 10-40 μm, the particle size of fly ash is 50-60 μm; the modulus of water glass is 1.5; and the particle size range of iron tailings is 10-100 meshes.

[0060] The present embodiment provides a method for preparing an alkali-activated grouting material, comprising: weighing slag, fly ash, iron tailings, calcium sulfoaluminate, anhydrite, sodium hydroxide, sodium silicate water glass, naphthalene-based water reducer, borax, sodium dihydrogen phosphate, polyether-modified silicon defoamer, 100,000 viscosity hydroxypropyl methylcellulose ether and 6 mm polypropylene fiber according to the above weight portions, mixing and stirring to obtain the grouting material.

[0061] The grouting material prepared in this embodiment has a 1d compressive strength of 20 MPa, a 3d compressive strength of 32 MPa, and a 28d compressive strength of 59 MPa. According to the "JCT985-2017 National Standard for Cement-Based Self-Leveling Mortar for Floors", the initial fluidity of the grouting material measured is 133 mm, the 20-min fluidity is 130 mm, and the volume deformation rate is 3 ten-thousandths of shrinkage.

[0062] Example 4

[0063] The present embodiment provides a composite stimulating grouting material, which includes the following raw materials in parts by weight: 250 parts of slag, 100 parts of fly ash, 1200 parts of iron tailings, 200 parts of calcium sulfoaluminate, 100 parts of anhydrite, 15 parts of sodium hydroxide, 50 parts of sodium silicate water glass, 8 parts of naphthalene-based water reducer, 8 parts of borax, 4 parts of sodium dihydrogen phosphate, 0.2 parts of fatty acid defoaming agent, 0.2 parts of 200,000 viscosity hydroxypropyl methylcellulose ether, and 10 parts of carbon fiber.

[0064] Among them, the particle size of slag is 10-40 μm, the particle size of fly ash is 50-60 μm; the modulus of water glass is 1.5; and the particle size range of iron tailings is 10-100 meshes.

[0065] The present embodiment provides a method for preparing an alkali-activated grouting material, comprising: weighing slag, fly ash, iron tailings, calcium sulfoaluminate, anhydrite, sodium hydroxide, sodium silicate water glass, naphthalene-based water reducer, borax, sodium dihydrogen phosphate, fatty acid defoaming agent, 200,000 viscosity hydroxypropyl methylcellulose ether and carbon fiber according to the above weight portions, mixing and stirring to obtain the grouting material.

[0066] The grouting material prepared in this embodiment has a 1d compressive strength of 23 MPa, a 3d compressive strength of 36 MPa, and a 28d compressive strength of 61 MPa. According to the "JCT985-2017 National Standard for Cement-Based Self-Leveling Mortar for Floors", the initial fluidity of the grouting material measured is 135 mm, the 20-min fluidity is 131 mm, and the volume deformation rate is 2.5 ten-thousandths of shrinkage.

[0067] Example 5

[0068] The present embodiment provides a composite stimulating grouting material, comprising the following raw materials in parts by weight: 450 parts of slag, 250 parts of fly ash, 400 parts of iron tailings, 300 parts of calcium sulfoaluminate, 70 parts of anhydrite, 25 parts of sodium hydroxide, 70 parts of sodium silicate water glass, 12 parts of naphthalene-based water reducer, 5 parts of borax, 3 parts of sodium dihydrogen phosphate, 0.6 parts of polyether modified silicon defoamer, 0.2 parts of 100,000 viscosity hydroxypropyl methylcellulose ether, and 10 parts of 6mm polypropylene fiber.

[0069] Among them, the particle size of slag is 10-40 μm, the particle size of fly ash is 50-60 μm; the modulus of water glass is 1.7; and the particle size range of iron tailings is 10-100 meshes.

[0070] The present embodiment provides a method for preparing an alkali-activated grouting material, comprising: weighing slag, fly ash, iron tailings, calcium sulfoaluminate, anhydrite, sodium hydroxide, sodium silicate water glass, naphthalene-based water reducer, borax, sodium dihydrogen phosphate, polyether-modified silicon defoamer, 100,000 viscosity hydroxypropyl methylcellulose ether and 6 mm polypropylene fiber according to the above weight portions, mixing and stirring to obtain the grouting material.

[0071] The grouting material prepared in this embodiment has a 1d compressive strength of 23 MPa, a 3d compressive strength of 37 MPa, and a 28d compressive strength of 65 MPa. According to the "JCT985-2017 National Standard for Cement-Based Self-Leveling Mortar for Floors", the initial fluidity of the grouting material measured is 135 mm, the 20-min fluidity is 131 mm, and the volume deformation rate is 3.7 ten-thousandths of shrinkage.

[0072] Comparative Example 1

[0073] The comparative example provides a composite stimulating grouting material, which includes the following raw materials in parts by weight: 350 parts of slag, 150 parts of fly ash, 800 parts of iron tailings, 100 parts of anhydrite, 20 parts of sodium hydroxide, 60 parts of water glass, 10 parts of naphthalene-based water reducer, 5 parts of borax, 3 parts of sodium dihydrogen phosphate, 0.2 parts of polyether modified silicon defoamer, 0.3 parts of 100,000 viscosity hydroxypropyl methylcellulose ether, and 2 parts of 6mm polypropylene fiber.

[0074] The grouting material prepared in this comparative example has a 1d compressive strength of 13 MPa, a 3d compressive strength of 23 MPa, and a 28d compressive strength of 45 MPa. According to the "JCT985-2017 National Standard for Cement-Based Self-Leveling Mortar for Floors", the initial fluidity of the grouting material measured is 1360 mm, the 20-min fluidity is 133 mm, and the volume deformation rate is 15 ten-thousandths of shrinkage.

[0075] By comparing the fluidity and volume stability of the grouting materials of Examples 1 to 5 with those of the grouting material of Comparative Example 1, it can be seen that the fluidity and volume stability of the grouting materials of Examples 1 to 5 are better than those of the grouting material of Comparative Example 1. It can be seen that the grouting materials disclosed in the present application have better fluidity and volume stability than traditional grouting materials.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite stimulating grouting material, characterized in that: The invention comprises the following raw materials in parts by weight: 300-700 parts of a precursor, 50-400 parts of an active activator, 400-1200 parts of solid waste aggregates, and 5-100 parts of an additive; wherein the precursor is a mixture of slag and fly ash in a mass ratio of 1:0.2-1:1.5; and the active activator is a mixture of calcium sulfoaluminate, gypsum, sodium hydroxide, and sodium silicate water glass in a weight ratio of 200-300:50-100:15-25:50-70.

2. The composite excitation grouting material according to claim 1, characterized in that: The particle size of the slag is 5 to 45 μm, and the particle size of the fly ash is 10 to 100 μm.

3. The composite excitation grouting material according to claim 1, characterized in that: The modulus of the sodium silicate water glass is 1.2-1.7; the gypsum is one or more of anhydrite, dihydrate gypsum and hemihydrate gypsum.

4. The composite excitation grouting material according to claim 1, characterized in that: The auxiliary agent is a mixture of naphthalene water reducing agent, borax, sodium dihydrogen phosphate, defoaming agent, cellulose ether and fiber in a mass ratio of 8-12:5-8:1-4:0.2-0.6:0.1-0.3:2-10.

5. The composite excitation grouting material according to claim 4, characterized in that: The cellulose ether is one or more of 400 viscosity hydroxypropyl methyl cellulose ether, 100,000 viscosity hydroxypropyl methyl cellulose ether, and 200,000 viscosity hydroxypropyl methyl cellulose ether.

6. The composite excitation grouting material according to claim 4, characterized in that: The defoamer is one or more of a mineral oil defoamer, a polyether-modified silicon defoamer and a fatty acid defoamer.

7. The composite excitation grouting material according to claim 4, characterized in that: The fiber is one or more of polypropylene fiber, basalt fiber and carbon fiber.

8. The composite excitation grouting material according to claim 1, characterized in that: The solid waste aggregate is iron tailings sand.

9. The composite excitation grouting material according to claim 8, characterized in that: The particle size of the iron tailings sand ranges from 10 to 150 meshes.

10. A method for preparing a composite excitation grouting material, characterized in that: include: The composite activated grouting material is obtained by weighing the precursor, the active activator, the solid waste aggregate and the additive according to the weight proportions described in any one of claims 1 to 9, and then mixing the precursor, the active activator, the aggregate and the additive.